The Role of Memory in the English as a Second Language Classroom (Bridging Cultures, 2019)
In the recent years, memory has been frequently disregarded as a tool to learn as it isconsidered a vehicle that makes students acquire temporary information and deprived of allmeaning. However, memory could be the tool that leads to effective, meaningful andconsequently permanent learning. Nowadays, research on the brain and its areas inconnection with learning has led to consider the benefits of taking these areas into account inthe ESL field. The various processes memory provides learners with during each learningepisode should be taken into account in order to provide students with a selection of activitiesaccording to the way in which these processes occur. The aim of this paper is to analyse howteachers use memory, memory-friendly approaches and activities in the classroom to fosterthe real role of memory: effective learning.
Keywords: Brain; ESL; Secondary School; Effective Learning; Memory; Lesson Plan; Approaches; Activities